2013
DOI: 10.1038/srep01021
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancies promoting photoelectrochemical performance of In2O3 nanocubes

Abstract: This work reports a facile method for preparing the new photoactive In2O3 films as well as their implementation in photoelectrochemical (PEC) application. We firstly investigated the relationship between oxygen vacancies (VO) and PEC performance and revealed a rule between them. We found that the optimized In2O3−n sample yielded a photocurrent density up to 3.83 mA/cm2 in 1 M Na2SO4 solution under the solar illumination. It also gave efficiency as high as 75% over 400 nm in the incident-photon-to-current-conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
321
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(344 citation statements)
references
References 52 publications
22
321
0
1
Order By: Relevance
“…[49] As uitable amount of OVs can optimize the PECp erformance.W eu se am ixed gas of 5% H 2 and 95 %A rt os trengthen the reducinga tmosphere; thus, H-BiVO 4Àx possesses ar elatively highera mount of OVs than A-BiVO 4 ,r esulting in superior photocurrent enhancement. [36] The fact that OVs induced throughh ydrogen treatment enhanced the charge-transportp roperties of BiVO 4 can be experimentally confirmed by comparing photocurrents obtained by back-side andf ront-side light illuminations. It has been shown that BiVO 4 electrodes generate ah igher photocurrent with back illumination than with front illumination, because the back-side illumination generates electron-hole pairs near the back contact, whereas front-side illumination generatese lectron-hole pairs near the electrode surface facing the electrolyte (Figure 4).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…[49] As uitable amount of OVs can optimize the PECp erformance.W eu se am ixed gas of 5% H 2 and 95 %A rt os trengthen the reducinga tmosphere; thus, H-BiVO 4Àx possesses ar elatively highera mount of OVs than A-BiVO 4 ,r esulting in superior photocurrent enhancement. [36] The fact that OVs induced throughh ydrogen treatment enhanced the charge-transportp roperties of BiVO 4 can be experimentally confirmed by comparing photocurrents obtained by back-side andf ront-side light illuminations. It has been shown that BiVO 4 electrodes generate ah igher photocurrent with back illumination than with front illumination, because the back-side illumination generates electron-hole pairs near the back contact, whereas front-side illumination generatese lectron-hole pairs near the electrode surface facing the electrolyte (Figure 4).…”
Section: Resultsmentioning
confidence: 72%
“…The OVsf unction as shallow donors in BiVO 4 ,facilitating the excitation of electrons by forming an ew energy level in the band gap, [36] resulting in improvede lectrical conductivity and PEC performance. Furthermore, Ni-B i plays ac rucial role in catalyzing PEC water oxidation with BiVO 4 .I ti nhibits the recombination of electron-hole pairs generateda tB iVO 4 by effectively mediating the hole transfer,w herein ac hange in the Ni oxidation state from lower (Ni 2 + andN i 3 + )t oh igher states (Ni 3 + and Ni 4 + )o ccurs.…”
Section: Resultsmentioning
confidence: 99%
“…The shoulder peak at approximately 532 eV is known to be a result of oxygen vacancies. [19,53,54] Oxygen anions are strongly deshielded because of incomplete ligand shells around neighboring metal cations and exhibit higher XPS binding energies. Deconvolution of the O 1s spectra (see Figure S14) shows that the intensity of the shoulder peak at 532 eV relative to that of the main oxide peak at 530 eV increases from 0.64 for sample A to 0.98 for sample B; this confirms an increased number of oxygen vacancies following hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…4b). This doublet corresponds to In3d 3/2 and In3d 5/2 states and their peaks for LCI-0 (444.8 and 452.5 eV) indicates that In valency is mainly +3 in the LCI-0 system [34,35]. As Ca 2+ is doped in LaInO 3 system (LCI-10), the peak shifting towards lower binding energy (B.E.)…”
Section: Xps Analysismentioning
confidence: 93%